A Global Assessment of Copper, Zinc, and Lead Isotopes in Mineral Dust Sources and Aerosols - Schleicher, Nina J.; Dong, Shuofei; Packman, Hollie; Little, Susan H.; Ochoa Gonzalez, Raquel; Najorka, Jens; Sun, Youbin; Weiss, Dominik J. (Frontiers in Earth Science, 2020)
The stable isotope compositions of Cu and Zn in major geochemical reservoirs are increasingly studied with the aim to develop these isotope systems as tools to investigate the global biogeochemical cycles of these trace metals. The objectives of the present study were (i) to expand the range of Cu, Zn, and Pb isotope compositions of mineral dust by analyzing samples from major mineral dust sources in Asia and Africa (Chinese Loess Plateau, Chinese deserts, Thar desert, Sahel region) and (ii) to assess the potential impact of human activities on the isotope composition of aerosols by synthesizing published Cu and Zn isotope compositions in aerosols and natural and anthropogenic sources. For the newly analyzed mineral dust areas in Asia and Africa, δ65CuNIST−976 values range from −0.54 to +0.52‰, δ66ZnJMC−Lyon values from −0.07 to +0.57‰, and 206Pb/204Pb values from 18.522 to 19.696. We find a significant geographic control with samples from the Thar Desert having the heaviest isotopic compositions (δ65CuNIST−976 = +0.48 ± 0.06‰, δ66ZnJMC−Lyon = +0.49 ± 0.11‰) and samples from the Sahel and the Badain Jaran desert having the lightest Zn isotope composition (δ66ZnJMC−Lyon = +0.19 ± 0.15‰ and +0.07 ± 0.07‰, respectively). We find important variations in the isotope signatures between particle size fractions with heavier isotopic compositions in the smallest and largest particle size fractions and lighter isotopic compositions in the mid particle size fractions. Associations with the mineralogical composition are less clear. Newly analyzed aerosol samples for Beijing and Xi'an show δ65CuNIST−976 values of +0.29 ± 0.19‰ and +0.16 ± 0.04‰, δ66ZnJMC−Lyon values of −0.36 ± 0.04‰ and +0.02 ± 0.06‰, and 206Pb/204Pb values of 18.129 ± 0.003 and 18.031 ± 0.003, respectively. Based on a synthesis of published and novel data, we suggest improved ranges and mean values for the isotopic composition of mineral dust from selected locations in Asia and Africa and of anthropogenic sources such as non-exhaust traffic emissions, combustion, electroplating and galvanization. This should serve as a valuable reference for future studies using these isotope systems. This paper demonstrates univocally that human activity introduces a wide range of Zn isotope compositions into the atmospheric environment and, thus, impacts the biogeochemical cycle of Zn.